2008
DOI: 10.1007/s00421-008-0828-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial differences in sensible and latent heat losses under a bicycle helmet

Abstract: This research aims at quantifying spatial gradients in skin temperature and sweat production under a bicycle helmet. Distribution of sweat production, skin temperature and air temperature was measured at different positions under a bicycle helmet on five male and four female test persons. Effort level was 100 and 150 watt for men (low and high effort level) and 80 and 120 W for women (low and high effort level). Skin temperatures were found to be spatially different (P < 0.05): frontal and lateral region varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Constant steady state sweat production on a human head, as described in literature (Takano et al, 1996;De Bruyne et al, 2008;Machado-Moreira et al, 2008b), showed similar results compared to this study. This allowed qualitative validation of the presented steady state sweat production data.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Constant steady state sweat production on a human head, as described in literature (Takano et al, 1996;De Bruyne et al, 2008;Machado-Moreira et al, 2008b), showed similar results compared to this study. This allowed qualitative validation of the presented steady state sweat production data.…”
Section: Discussionsupporting
confidence: 90%
“…Researches towards spatial gradients in latent heat loss on a human head (Machado-Moreira et al, 2008b;De Bruyne et al, 2008) have analyzed static experimental results (constant steady state sweat production). These studies did not consider the dynamics of the sweat response such as the time delay between a change in work rate and the onset of sweating and the time constant describing how fast the sweat rate changes.…”
Section: Introductionmentioning
confidence: 99%
“…Across all test conditions, there was an average temperature difference of 9.2 °C between thermocouples with a maximum temperature difference of 25 °C between two points of the head in the TT helmet, as shown in Figure 2. This is a much larger discrepancy than found by De Byrne et al [6]. One cause of the variation in temperature is due to the frontal thermocouples generally being located below the helmet brim and directly in the airflow, producing much lower temperature values compared to points completely insulated from both the free-stream and alternative cooling flows provided by the helmets.…”
Section: Thermal Testingmentioning
confidence: 60%
“…A study by De Bruyne et al [6] observed spatial differences of up to 5.5 °C between different areas of the head. Hence a focus in the design of this headform was for the ability to adequately replicate and observe the various hot and cold regions that a human head would experience during cycling.…”
Section: Materials Of Constuctionmentioning
confidence: 96%
“…This has motivated a number of studies on characterizing and optimizing thermal properties of such headgear (Fonseca, 1974;Reischl, 1986;Spaul et al, 1987;Abeysekera et al, 1991;Liu and Holmer, 1995;Liu, 1997;Liu et al, 1999;Hsu et al, 2000;Holland et al, 2002;Brühwiler, 2003;De Bruyne et al, 2008). As a result, headgear improvement concepts were proposed to improve temperature perception and thermal comfort (Abeysekera and Shahnavaz, 1988;Holland et al, 2002).…”
Section: Introductionmentioning
confidence: 99%